La perfidia laboral como forma de establecer una relación laboral y los derechos vulnerados a los trabajadores en la ciudad de Guaranda año 2021. - Chimbo Pazmiño, Daniela Alejandra (2023)
The present investigation originates when the employer, by way of deception, proceeds to hire the worker when, in addition to signing or not the employment contract, he is also required to sign a blank executive title in order to protect the business assets. That is why this work is developed from an analytical and interpretive point of view according to the reality that the city of Guaranda, Bolívar province, experiences in the face of the constant and evident violation of constitutional and labor rights, which prevents a life from being guaranteed. worthy, enjoying job stability and fair remuneration for the activities performed. The subject of study, such as labor perfidy, has undoubtedly generated ignorance not only in society but also in legal professionals, the vast majority of whom indicated that they had no knowledge of the aforementioned subject. These and other questions will be reflected thanks to the surveys and all kinds of informative data collection carried out in the Guarandeño population, both to workers, employers, lawyers and citizens in general, obtaining results that allow generating a broad and detailed study of the subject. tackled and the social problems that it entails. Complying with the requirements established to support this research, an attempt has been made to address the greatest number of relevant topics, as stated in the theoretical framework, the methodology carried out is subsequently indicated, mainly the methods and types of analytical, deductive, bibliographical, and quantitative research. and legal, emphasizing the silver problem from a social perspective, which has served to acquire multiple knowledge of the current topic, allowing to obtain and generate conclusions and recommendations that are expected and accepted in their entirety since they will be very useful for future research in the 5 labor field and above all to demonstrate the existing legal gaps in the national justice and thus provide a solution to the approach to the problem that this work is based on.